Futurama. Business Forecasting and the Dynamics of Capitalism in the Interwar Period - Laetitia Lenel (Humboldt University Berlin, 2018)
The recognition of the key importance of economic stability after World War I sparked interest in business forecasting on both sides of the Atlantic. This article explores the creation and the rapid international and domestic dissemination of the Harvard Index of General Business Conditions in the early 1920s, which contemporaries celebrated as the first "scientific" approach to business forecasting. Drawing on multi-site archival research, the paper analyses the extension of the index by an information-exchange-based method in the 1920s and traces its influence on the survey-based forecasting approach employed by American companies in the 1930s. Engaging with the current debate on the temporal order of capitalism, the article argues that business forecasting was not only a means of stabilizing capitalism, but a factor and an indicator of a change in the dynamics of capitalism in the interwar period.
urn:nbn:de:kobv:11-110-18452/19412-9
Keywords: B00; B10; B20; B41; N01; N40; 330; Prognose; Konjunkturforschung; Kapitalismus; Konsumforschung; Wirtschaftskrisen; Wissensgeschichte; Zukunft; forecasting; future; business cycle research; capitalism; consumer research; historical epistemology; material practices; Harvard Economic Service; London and Cambridge Economic Service; League of Nations; General Motors